2015
DOI: 10.1177/1091581815583678
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Week Toxicity Study of Methionine in Male Rats

Abstract: To examine 4-week toxicity of l-methionine (methionine), 5-week-old Fisher strain male rats were fed on diets containing 0, 0.1, 0.3, 0.9, 2.7 (w/w) of added methionine. Although no deaths were recorded, the highest dose of methionine (2.7% [w/w] of diet) reduced food intake and significantly suppressed growth rate. Growth suppression was characterized by an increase in hemolysis, splenic, and hepatic accumulation of hemosiderin, hemolytic anemia, and promotion of hematopoiesis. Other changes observed in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…The hyperhomocysteinemia induced by methionine administration leads to increased production of free radicals and inflammation markers in macrophages of the mouse peritoneum (5). An in vitro and in vivo study on rats showed the alteration of oxidative stress parameters after the methionine administration (6), and hemosiderin accumulated in rat hepatocytes after a four-week methionine treatment (7). The occurrence of hyperhomocysteinemia was also reported in a population of patients with inflammatory bowel disease after an oral overload with methionine (8).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The hyperhomocysteinemia induced by methionine administration leads to increased production of free radicals and inflammation markers in macrophages of the mouse peritoneum (5). An in vitro and in vivo study on rats showed the alteration of oxidative stress parameters after the methionine administration (6), and hemosiderin accumulated in rat hepatocytes after a four-week methionine treatment (7). The occurrence of hyperhomocysteinemia was also reported in a population of patients with inflammatory bowel disease after an oral overload with methionine (8).…”
Section: Introductionmentioning
confidence: 83%
“…limiting the production of reactive oxygen species (6,7). Methionine removes metabolic waste products from the liver and can thus decrease the risk of hepatic and arterial steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…l ‐Met being an essential amino acid, its intake needs to be regulated and its systemic levels should be optimized so that it can maintain normal body homeostasis. Recent studies show that methionine intake up to 91 mg kg –1 body of weight in humans and 705 mg kg –1 body of weight per day in an animal is well tolerated to sustain a healthy life . In view of this, we designed in vivo study of l ‐Met‐S in diabetic animals and selected the dose of l ‐Met for our animal study.…”
Section: Discussionmentioning
confidence: 99%
“…l ‐Met along with other methyl donors has been shown to improve glucose tolerance and insulin sensitivity in offspring of high‐fat diet (HFD) fed dams, reduce fatty liver in high fat‐sucrose diet fed rats via alteration in DNA methylation, and activate AMPK and prevent the Non‐alcoholic fatty liver disease (NAFLD) in obese mice . However, there is a risk of an increase in homocysteine level (a risk factor for cardiovascular disease) and decreased body weight with increased intake of l ‐Met . There are reports suggesting that methionine restriction can improve insulin sensitivity, glucose homeostasis, oxidative stress, lipid metabolism, and longevity .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation